SPIRITUAL COUNSELING APPROACHES IN RELIGIOUS POLICY FOR HANDLING ROHINGYA REFUGEES - Mubarak, Azhar; Azka, Ibnu (The Ministry of Religious Affairs, The Republic of Indonesia, 2024)
This research aims to explore and analyze the application of the spiritual counseling approach in religious policies for handling Rohingya refugees.Rohingya refugees who have experienced trauma and psychological stress due to genocide and oppression in Myanmar need special assistance in recovering their mental health. A spiritual counseling approach, which integrates religious values in the counseling process, is considered effective for overcoming psychosocial problems faced by refugees. This study uses a literature study research method by collecting and analyzing various secondary sources such as books, journal articles, policy reports and official documents. The results of this research show that spiritual counseling can have a significant influence in recovering the mental health of Rohingya refugees by restoring their psychological function and strengthening their religious values. The implementation of spiritual counseling carried out by various institutions, such as UNHCR, IOM, and local religious organizations, hass hown a positive impact in reducing anxiety, depression and trauma experienced by refugees. In addition, the people of Aceh who have the same religious background as the Rohingya refugees provide strong support for this program. In conclusion, the spiritual counseling approach through religious policies is an effective strategy for psychosocial management of Rohingya refugees , especially in the context of mental health recovery. This research recommends increasing cooperation between governments, international organizations, and religious institutions to expand the reach and effectiveness of spiritual counseling programs for refugees.